GENERATION AND MARKETING COMMUNICATION: GENERATIONS’ ATTITUDES TOWARDS DIGITAL MARKETING ELEMENTS - Emel SARITAŞ (Fırat University, 2019)
It is very important that businesses should not be ignored to keep abreast of evolving technology when the contemporary world of communication evolves incredibly and considering the possibilities of using innovations in communication in marketing activities. However, whilst businesses incorporate innovations to their mix of marketing, the identification of the characteristics of the mass that they can reach with these communication elements should be considered as another important field of activity. The age factor, which is considered as the most basic criterion for defining the target group, gives the opportunity to provide more clear information to the businesses when considered as the same living group. Generations have similar thoughts and attitudes because they are influenced by socio-economic events of the same period. In this study, the use of digital communication elements and the attitudes of the generations towards these digital communication elements were analyzed according to the generations. As a result of research that have conducted especially on mobile phone, internet and social media usage; there is no difference in terms of mobile phone use among generations, but it found that there is a difference in terms of internet and social media usage. When assessed differences between generations in terms of attitudes towards messages that businesses use to communicate using digital marketing elements, it is conclude that there is no difference between generations for finding disturbing, safe and convenient but there is difference for informative and amusing attitudes. Within these findings, suggestions are given to business and marketing managers.